On statistical convergence of vector-valued sequences associated with multiplier sequences - Altinok, H.; Et, M.; Gökhan, A. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We introduce vector-valued sequence spaces w_∞(F, Q, p, u), w_1(F, Q, p, u), w_0(F, Q, p, u), S^q_u and S^q_0u, using a sequence of modulus functions and a multiplier sequence u = (u_k) of nonzero complex numbers. We give some relations for these sequence spaces. It is also shown that if a sequence is strongly u_q -Cesàro summable with respect to the modulus function, then it is u_q -statistically convergent.